On tracing attackers of distributed denial-of-service attack through distributed approaches - Wong, Tsz Yeung (ProQuest Dissertations & Theses, 2007)
The denial-of-service attack has been a pressing problem in recent years. Denial-of-service defense research has blossomed into one of the main streams in network security. Various techniques such as the pushback message, the ICMP traceback, and the packet filtering techniques are the remarkable results from this active field of research. The focus of this thesis is to study and devise efficient and practical algorithms to tackle the flood-based distributed denial-of-service attacks (flood-based DDoS attack for short), and we aim to trace every location of the attacker. In this thesis, we propose a revolutionary, divide-and-conquer trace-back methodology. Tracing back the attackers on a global scale is always a difficult and tedious task. Alternatively, we suggest that one should first identify Internet service providers (ISPs) that contribute to the flood-based DDoS attack by using a macroscopic traceback approach . After the concerned ISPs have been found, one can narrow the traceback problem down, and then the attackers can be located by using a microscopic traceback approach. For the macroscopic traceback problem, we propose an algorithm, which leverages the well-known Chandy-Lamport's distributed snapshot algorithm, so that a set of border routers of the ISPs can correctly gather statistics in a coordinated fashion. The victim site can then deduce the local traffic intensities of all the participating routers. Given the collected statistics, we provide a method for the victim site to locate the attackers who sent out dominating flows of packets. Our finding shows that the proposed methodology can pinpoint the location of the attackers in a short period of time. In the second part of the thesis, we study a well-known technique against the microscopic traceback problem. The probabilistic packet marking (PPM for short) algorithm by Savage et al. has attracted the most attention in contributing the idea of IP traceback. The most interesting point of this IP traceback approach is that it allows routers to encode certain information on the attack packets based on a pre-determined probability. Upon receiving a sufficient number of marked packets, the victim (or a data collection node) can construct the set of paths the attack packets traversed (or the attack graph), and hence the victim can obtain the locations of the attackers. In this thesis, we present a discrete-time Markov chain model that calculates the precise number of marked packets required to construct the attack graph. Though the PPM algorithm is a desirable algorithm that tackles the microscopic traceback problem, the PPM algorithm is not perfect as its termination condition is not well-defined in the literature. More importantly, without a proper termination condition, the traceback results could be wrong. In this thesis, we provide a precise termination condition for the PPM algorithm. Based on the precise termination condition, we devise a new algorithm named the rectified probabilistic packet marking algorithm (RPPM algorithm for short). The most significant merit of the RPPM algorithm is that when the algorithm terminates, it guarantees that the constructed attack graph is correct with a specified level of confidence. Our finding shows that the RPPM algorithm can guarantee the correctness of the constructed attack graph under different probabilities that the routers mark the attack packets and different structures of the network graphs. The RPPM algorithm provides an autonomous way for the original PPM algorithm to determine its termination, and it is a promising means to enhance the reliability of the PPM algorithm.